(untitled) (TSUL LEGAL REPORT, 2026)
This paper is dedicated to comparative analysis of the criminal legislation of Norway in framework of consideration of the mitigating factors and criminal defenses. The present research is provided overall explore of mitigation of sentence institute in accordance with the existing edition of the Penal Code of the Norway, announced on 20 of May, 2005 and fully entered into force on 1 of October, 2015 (Chapter 16 was entered into force from 7 of March, 2008) and the Criminal Code of the Republic of Uzbekistan, enacted on 22 of September, 1994 and entered into force from 1st of April, 1995, including the issues on determining the punishment for the criminal offences committed in a state of mental disorder as well as insanity and diminished responsibility, for incomplete offences and the criminal complicity, including criminal defenses, institutions on the withdrawal (voluntary refusal) from the commission of an offence and innocent harm. Pursuant to the results of the conducted analysis, similar and different sides of existing criminal laws have been clarified, decisions on the concluded analysis and final conclusion on the implementation of Norway’s some criminal law norms to the criminal law of the Republic of Uzbekistan has been provided.